2014
DOI: 10.4034/pboci.2014.144.08
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Oral Health: A Systematic Review

Abstract: Objective: To carry out a systematic review of the scientific literature addressing the possible association between food insecurity and oral health. Material and Methods: An electronic search limited to studies conducted with humans was performed in six databases (Pubmed, Web of Science, Scopus, Lilacs, BBO, Cochrane Library) and IADR abstracts, with no language or publication date restrictions. The search strategy resulted in 614 titles/abstracts. Seven cross-sectional studies were selected from this total. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…10 Both income and FI are related to dental caries. 5,11 FI, however, is also associated with income. Therefore, further studies are needed to identify the pathways by which FI and socioeconomic status contribute to poor health outcomes.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…10 Both income and FI are related to dental caries. 5,11 FI, however, is also associated with income. Therefore, further studies are needed to identify the pathways by which FI and socioeconomic status contribute to poor health outcomes.…”
Section: Introductionmentioning
confidence: 91%
“…Affirmative responses (yes = 1) are summed and the score ranges from 0 to 15. Based on this score, families are classified as follows: food security (score: 0), mild FI (score: 1-5), moderate FI (score: 6-10), and severe FI (score: [11][12][13][14][15]. 13 Income was analysed using the Brazilian monthly minimum wage (BMMW, equal to US$ 284 at the time the study was conducted) as the unit of analysis, which was divided by the number of residents in the home for the calculation of per capita household income.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, results found in Turkey [27] found that better economic condition is directly related to obesity among children, and a systematic review shows that economic difficulty can lead to increase vulnerability and health problems [28].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural, cultural and social factors are the main potential risk factors that play roles in dental caries development. The impact of dietary habits and diet quality on oral health have been broadly studied; however, research on food insecurity is limited 3 …”
Section: Introductionmentioning
confidence: 99%
“…The impact of dietary habits and diet quality on oral health have been broadly studied; however, research on food insecurity is limited. 3…”
mentioning
confidence: 99%